Market Entry Strategies : Internationalization Theories, Concepts and Cases of Asian High-Technology Firms: Haier, Hon Hai Precision, Lenovo, LG Electronics, Panasonic, Samsung, Sharp, Sony, TCL, Xiaomi - Glowik, Mario (De Gruyter Studium, 2016)
This textbook discusses the most important theories of internationalization, including Product Life-Cycle, Internalization, Location, Eclectic Paradigm, Uppsala, Network, and International New Venture concepts. These models are grounded to a considerable extent in the Transaction Cost Theory and the Resource-Based View as explained and illustrated in the book. Relevant market entry strategies, such as franchising, contract manufacturing, joint ventures, and others are explained and categorized in light of crucial determinants of international business decision making: hierarchical control of operations, the firm's proximity to the foreign market, the investment risk, and the factor of time. What makes this textbook novel and unique? Its framework combines theories and market entry strategies: each topicis applied to authoritative, real-life business case studies. Complex issues are explained in a manner that results in understanding. Various illustrations and tables help the reader comprehend the point being discussed. The case study focus on Asian firms delivers interesting insights into modern high-technology industries and changing global business dynamics. Market Entry Strategies serves as a vital source for internationally oriented bachelor, master, and MBA programs with strategy, marketing, and management lecture modules. Consequently, this publication is highly recommended for students and scholars; but it is also useful for business practitioners seeking to gain competitive advantages in international business. About the Author Mario Glowik teaches Bachelor, MBA and Master courses in Strategic management, International management, Strategic management in China and Europe, and International and Asian business at Berlin School of Economics and Law in Berlin. Find out more about Professor Glowik and the second edition of his Textbook Market Entry Strategies on Youtube!